Structural performance of glulam mengkulang timber beam with slotted-in steel plate bolted connection / Mohd Nizam Shakimon - Shakimon, Mohd Nizam (2022)
The connection plays a vital role in assembling the timber members to maintain stability and strength in the timber structure. The large deformation concept is adopted in the timber connection design to allow ductility failure instead of timber brittle failure, thus providing a higher lateral load-carrying capacity and structural stability. Since timber is a combustible material, the design of timber connections becomes more crucial to prevent premature failure due to fire loading. Additional designs for fire requirements are specified. Currently, European Yield Model (EYM) design theory is widely adopted to design timber connections at normal temperature and for fire requirements. However, the Malaysian Design Code for Timber (MS544) still lacks extensive specifications for determining the performance of tropical timber connections in a fire event. Therefore, this research aims to provide insight into the structural timber connections after exposure to a fire event for further study and reference. It specifically studies the structural performance of the slotted-in steel plate bolted connection in the engineered wood product (EWP) glued-laminated (glulam) timber beam after exposure to a standard fire. A modification to the extensive EYM theoretical model specified in Eurocode (EC) 5 for the fire is proposed to suit Malaysian tropical timber. It involved experimental tests under four-point bending and tensile loads for eighteen (18) glulam Mengkulang timber beams samples in 130mm x 150mm x 1400mm geometry specifications connected with slotted-in steel plate and bolts 12mm, 16mm, and 20mm diameters. The Mengkulang glulam timber beams samples were divided into groups 1 and 2. Group 1 consisted of eleven (11) samples tested in tensile, with nine (9) were performed at normal temperature, and two (2) were performed in a standard fire. The tensile test at normal temperature was performed until rupture to determine the samples ultimate load-carrying capacity. The tensile test in the standard fire was performed in a fire furnace by positioning the samples vertically, supported at the top end, and the bottom end was subjected to a static tensile load of 40% ultimate load-carrying capacity at normal temperature. The samples were exposed to fire, and the temperature was controlled to follow the standard fire curve specified in BS476-22. Group 2 consisted of seven (7) glulam timber beams tested in bending at normal temperature, with three (3) were tested after exposure to a 30-minute standard fire and cooled down to normal temperature. The results were further used to validate the computer simulation using the finite element method (FEM) for parametric study. After exposure to the standard fire, the experimental results showed the load-carrying capacity of the Mengkulang glulam timber beams under the four-point bending test reduced by 71.8%, 26.1%, and 47.6% for bolt diameters of 12mm, 16mm, and 20mm, respectively. Further investigations show that the glulam timber beams samples before exposure to the standard fire reached ductility failures. However, after exposure to the standard fire, the experimental results show the brittle failure in timber. A linear fitting was established to modify the EYM specified in Eurocode 5 to determine the load-carrying capacity of glulam Mengkulang timber bolted connection after exposure to the standard fire, thus proposing the equation for decay constant.